Naturalization of an alien ancient fruit tree at a fine scale: Community structure and population dynamics of Cydonia oblonga in China. Issue 1 (6th January 2023) - Xie, Yong; Li, Jiaxiang; Zhao, Lijuan; Liu, Wenqian; Gong, Qunlong; Deng, Mengda; Zhao, Mohan; Huang, Song
Abstract: Naturalized plants play pivotal roles in local plant biodiversity and ecological functions; however, the drivers of naturalization remain poorly understood at a fine scale. Thus, understanding the processes of the development and dominance of alien plants in local natural habitats is of paramount importance. In the present study, we report for the first time the naturalization of Cydonia oblonga in China based on community structure and population dynamics at a fine scale. We conducted a comprehensive survey of the species through field community investigations, interviews, and a literature review. Cydonia oblonga is an ancient fruit tree with a long introduction history of over 4500 years worldwide and a cultivation history of over 2500 years in China. We analyzed C. oblonga community structure using the spatiotemporal substitution method and quantitatively analyzed population dynamics using a static life table, survivorship curve, and time series model to explore the naturalization processes. The following results were obtained. (i) The community comprised 31 coexisting vascular plant species (16 woody and 15 herbaceous species) belonging to 28 genera in 20 families. Rosaceae and Asteraceae were the two most dominant families. (ii) All individuals in the shrub layer as well as the C. oblonga population exhibited a roughly inverted J‐shaped basal diameter distribution. A complete age structure was noted, and the survival curve was classified as Deevey type II. According to time series analysis, the population is estimated to increase in the future, specifically of medium and large individuals. (iii) Religious exchange, potent resource competitiveness, and similarity with the native habitat may be the major drivers of the introduction and successful naturalization of C. oblonga . These results suggest that alien species closely related to native ones are more likely to invade, naturalize, and dominate communities in local habitats. Abstract : We report for the first time the naturalization of Cydonia oblonga in China and East Asia based on community structure and population dynamics at a fine scale. We conducted a comprehensive survey of the species through field community investigation, interviews, and literature information. The results suggest that alien species closely related to native species are more likely to invade, naturalize, and become dominant species in local habitats, which strongly supports the "pre‐adaptation hypothesis" at a fine scale.